Optimalisasi Pemanfaatan Data Automatic Exchange of Information (AEOI) dalam Proses Bisnis Perpajakan: Tinjauan Persepsi dan Kendala pada Kantor Pelayanan Pajak - Adli Gumilang Herdi; Akhmad Nur Imtihanul Hikam; Errik Syahputra; M. Rafli Al Mubarok; Syifa Auliya Mahendra (Jurnal Ragam Pengabdian, 2026)
This study examines the optimization of Automatic Exchange of Information (AEOI) data utilization in tax administration by focusing on user perceptions and operational constraints at the implementation level. Although AEOI has contributed to expanding the tax base and increasing tax revenue, its effective use in day-to-day tax supervision remains dependent on data governance and organizational readiness at tax offices. This research employs a qualitative descriptive approach to obtain an in-depth understanding of AEOI data distribution and utilization in practice. Primary data were collected through semi-structured, in-depth interviews with three Account Representatives working at a Tax Service Office who directly use AEOI data in taxpayer supervision. Informants were selected using purposive sampling based on their direct involvement in handling AEOI data. The interview data were analyzed using thematic analysis to identify key themes related to data distribution, data quality perception, service quality, follow-up actions, encountered constraints, and the role of AEOI in tax administration processes. The findings indicate that AEOI data are distributed centrally through internal tax applications, enabling uniform access for implementation units. The data are perceived as accurate and complete in identifying taxpayers and financial assets, thereby supporting compliance supervision. However, delayed data availability, inefficient data formats, limited technical support, and the need for manual data verification reduce the practical relevance of the information. Despite these constraints, AEOI plays a significant role in strengthening tax supervision and supporting revenue collection